Akibat Hukum bagi Prajurit TNI Melakukan Tindak Pidana Desersi yang Diputus In Absentia dalam Praktek Pengadilan Militer III-14 Denpasar - I Wayan Kusuma Purwanta; Anak Agung Sagung Laksmi Dewi; Ni Made Sukaryati Karma (Jurnal Konstruksi Hukum, 2021)
The Unitary State of the Republic of Indonesia is a State of Law. Obligatory for Indonesian citizens to obey and obey the law, no exception for Soldiers of the Indonesian National Army. Apart from being subject to general legal rules such as the Criminal Code and also subject to special rules that only apply to soldiers of the Indonesian National Army, namely the Military Criminal Code and the Military Discipline Law Code. Discipline attitude is a basic milestone for TNI soldiers in carrying out their duties. If a TNI soldier lacks discipline in his life, it will lead to a criminal act. This study aims to explain the factors that cause TNI soldiers to commit the Esersion crime and to explain the legal consequences of the In Absentia decision for TNI soldiers who commit the crime of desertion. The method used is a juridical-empirical research method with a problem approach using case studies that are based on real events in the field without any deception and are pure in nature. The legal materials used are primary and secondary legal materials. The results of the study state that the legal consequence of In absentia a TNI soldier who commits the crime of desertion will remain on trial without the presence of the defendant and will be sentenced to imprisonment with additional penalties in the form of dismissal from military service and the factor that causes TNI soldiers to commit the crime of desertion is lack of discipline as a military soldier, the economy barely lives, is involved in a criminal act, is in debt and is influenced by environmental associations.